Spanning the genomics era: the vital role of a single institution biorepository for childhood cancer research over a decade - Zhou, Li; Catchpoole, Daniel (Translational Pediatrics; Vol 4, No 2 (April 28, 2015): Translational Pediatrics (Studies on Genetic Diseases for better therapies in Pediatrics), 2015)
The ‘genomics era’ is considered to have begun with the commencement of the Human Genome Project. As translational genomic studies can only be established when human tissue samples are available for analysis, biospecimens are now proven to be an essential element for their success. During the genomics era the necessity for more extensive biobanking infrastructure has been highlighted. With the increased number of genomic studies into cancer, it is considered that the availability of biospecimens will become the rate limiting step. Despite the efforts in international biobanking, translational genomics is hampered when there low numbers of biospecimens for a particular rare diseases and is most apparent for paediatric cancer. As there is a call for biobanking practice to be responsive to the current experimental needs of the time and for more expansive systems of tissue procurement to be established we have asked the question what role does a single institution biorepository play in the current highly networked world of translational genomics. Here we describe such a case. The Tumour Bank at The Children’s Hospital at Westmead (TB-CHW) in the western suburbs of Sydney was formally established in 1998 as a key resource for translational paediatric cancer research. During the genomics era, we show that the TBCHW has developed into a key biospecimen repository for the cancer research community, during which time it has increasingly found itself having a vital role in the establishment of translational genomics for paediatric cancer. Here we detail metrics that demonstrate how as a single institution biorepository, the TB-CHW has been a strong participant in the advancement of translational genomics throughout the genomics era. This paper describes the significant contribution of a single institutional hospital embedded tumour biobank to the genomic research community. Despite the increased stringencies placed on biobanking practice, the TB-CHW has shown that a single institution biorespository can have a consistent and effective contribution to translational research into rare paediatric malignancy demonstrating its long term benefit throughout the genomics era.